Create a Device for Identifying the Location of Alzheimer's Patients - Kiki Rezki Lestari; Muhammad Difa Ramadhan; Sunartoto Gunadi (Global Writing Academica Researching & Publishing, 2022)
The elderly are unavoidably at a higher risk of disease. Alzheimer's disease is one of the most common conditions that affect the elderly. Alzheimer's disease is a brain disease caused by cell damage that results in memory and thinking ability loss as well as behavioral changes. Three satellites are used in this process, with two forming an imaginary line from the user and the third determining the user's position. This module can be integrated by a variety of antennas connected to the U.FL connector to capture satellite signals. The response from the module is sent from the coordinate data from Latitude from the test site based on the tests that have been completed. Due to the limited ability to capture the 800 L SIM module signal in comparison to smartphones commonly used today, network connection problems in closed rooms or places far from signal transmitting towers are the most frequently encountered during testing.